Gambaran Mean Arteri Pressure (MAP) dan Protein Urine Untuk Skrining Preeklampsi pada Ibu Hamil - Zainiyah, Zakkiyatus; Susanti, Eny; Harahap, Dewi Anggriani (Jurnal Kesehatan Komunitas, 2024)
Early detection of preeclampsia in pregnant women with BMI, ROT, and MAP aims to screen for risk factors for preeclampsia. If pregnant women are found to have risk factors, it can be prevented so that complications do not occur during pregnancy and childbirth. Accompaniment or follow-up can be done for the mother. pregnant with risk factors. The study aimed to analyze the Mean Arterial Pressure (MAP) and Urine Protein for preeclampsia screening in pregnant women. The results of the study were that most of the ages were not at risk as many as 185 people 88%, some parity multigravida mothers were 137 people 65%, and some third-trimester pregnant women were 115 people 54.7%. Most of the body mass index is obese 53.8% and blood pressure is mostly normal as much as 95.1%. MAP ≥ 90 22% and urine protein examination results in 6.68% positive, pregnant women should routinely have their pregnancies checked, especially at Integrated Ante Natal Care, so they can control blood pressure and regulate their eating patterns to avoid blood pressure increases such as by reducing consumption of salt, fatty and fried foods. Screening in pregnant women should be carried out continuously to reduce the incidence of preeclampsia in pregnant women.